2019
DOI: 10.1080/1828051x.2019.1674701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carcass traits, meat quality and expressions of MyHCs in muscles between Mashen and Large White pigs

Abstract: The aim of this study was to evaluate the differences in carcase traits, meat quality and muscle characteristics (mean fibre diameter and MyHCs levels of expression) between Mashen and Large White pigs. A total of 60 pigs (30 Mashen pigs and 30 Large White pigs, half male and half female in each breed) were used in this experiment. Results showed that Mashen pigs exhibited lower slaughter weight, reduced back-fat thickness, reduced loin eye area and lower lean meat ratio than Large White pigs (p < .05). Meat f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
2
13
0
2
Order By: Relevance
“…MYH7 , MYH2 , MYH4 , and MYH3 are the specific genes of type I, type IIA, type IIB, and type IIX myofibers, respectively ( Schiaffino and Reggiani, 2011 ). In a previous study, the specific gene expression of type I and type IIA myofiber in MS pigs was significantly higher than that in LW pigs, whereas the specific gene expression of type IIB myofiber was higher in LW pig ( Guo et al, 2019 ). In the present study, the expression of MYH7 in MS pigs was higher than that in LW pigs at 0 day, but there were no significant differences at 90 and 180 days.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…MYH7 , MYH2 , MYH4 , and MYH3 are the specific genes of type I, type IIA, type IIB, and type IIX myofibers, respectively ( Schiaffino and Reggiani, 2011 ). In a previous study, the specific gene expression of type I and type IIA myofiber in MS pigs was significantly higher than that in LW pigs, whereas the specific gene expression of type IIB myofiber was higher in LW pig ( Guo et al, 2019 ). In the present study, the expression of MYH7 in MS pigs was higher than that in LW pigs at 0 day, but there were no significant differences at 90 and 180 days.…”
Section: Discussionmentioning
confidence: 78%
“…A previous study showed that the growth rate of MS pigs was slower than that of LW pigs ( Zhao et al, 2017 ; Guo et al, 2019 ). We clustered the longissimus thoracis muscle tissues sampled at three time points (early, middle, and later development stages).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Currently, circRNA research focuses on various diseases, particularly malignant tumors, with circRNA expression in, and effect on, pig muscle development not yet reported. Here, we selected the Large White (LW) pig, a Western commercial breed, and the Mashen (MS) pig, a Chinese local breed, based on the differences in muscle ber diameter, density, intramuscular fat content, at different developmental stages between these two pig breeds [30,31]. RNA sequencing technology and bioinformatics methods were applied to analyze the differential expression of circRNA (DEcircRNA) and its regulatory network during different developmental stages of these two breeds (1, 90, and 180 days old).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the growth rate of MS pigs was slower than that of LW pigs (Zhao et al, 2017;Guo et al, 2019).…”
Section: Candidate Genes Responsible For the Slower Growth Rate Of Mamentioning
confidence: 95%